(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
This research provides a scientific and cognitive addition to the studied basalt rocks from the petrographic point of view. Fifteen rock slides representing the studied rocks from three selected sites were studied from the Qalaat Al-Housen geological expanse at a scale of 1 / 50,000 with a polarized microscope. The petrographic variations of the studied rocks were determined depending on the phenocrysts of the olivine and pyroxene minerals. And plagioclase. They are olivine basalt and basalt. Keywords: Baselt, petrographic, Anaz, Qalatiyah, Al mouzeina.